A multi-centred pilot randomised controlled trial of learning through play plus culturally adapted cognitive behaviour therapy for treating postnatal depression in Nigerian women - Jidong, Dung Ezekiel; Ike, Tarela Juliet; Taru, Maigari Yusuf; Pwajok, Juliet Yop; Nwoga, Charles Nnaemeka; Jidong, John Ezekiel; Francis, Christopher; Mwankon, Shadrack Bitrus; Haruna, Karick; Dagona, Zubairu; Husain, Nusrat (Frontiers in Psychiatry, 2025)
BackgroundAbout 13% of women globally experience postnatal depression with adverse implications for the mothers and their children. In Nigeria, there is limited access to evidence-based culturally appropriate care for mothers affected by postnatal depression.MethodsThis study was a multi-centre, two-arm, parallel-group, single-blind, individually randomised controlled trial design adopted to test the feasibility, cultural appropriateness and acceptability of Learning Through Play plus Culturally adapted Cognitive Behaviour Therapy (LTP+CaCBT). The LTP+CaCBT is a 12-session (90 minutes each) intervention to treat postnatal depression, and this was compared with the Enhanced Treatment As Usual (ETAU). Sixty-six mother-child pairs across three centres who scored >5 on the Patient Health Questionnaire (PHQ-9) were recruited for the study and randomised to either the LTP+CaCBT experimental or ETAU control groups. Data were collected at various time points (baseline, end of intervention and 3 months post-enrolment) and analysed using appropriate descriptive and inferential statistics. N = 3 focus groups comprising 11 participants each and n = 18 individual interviews were conducted to explore participants’ experiences engaging with the intervention. Interviews were transcribed verbatim and analysed using interpretative phenomenological analysis.ResultThe LTP+CaCBT group (n=33) recorded a high participants’ recruitment, participation and retention rate of 94% across 12 sessions. Satisfaction with intervention (LTP+CaCBT, 97%; ETAU, 34.4%). reduction in postnatal depression was higher in LTP+CaCBT on PHQ-9 Md = 3.00 with z= -4.935; compared to ETAU, Md=4.00 with z= -2.556. Improvement was also recorded for the anxiety and social support level; there was no improvement for the control group, as the scores remained the same. Themes identified from the qualitative dataset showed positive behaviour management, enhanced mother-child interaction and relationship, modification of negative thought processes, positive experience and relationship formation.ConclusionThe LTP+CaCBT intervention is shown to be acceptable and culturally appropriate whilst indicating potential clinical effectiveness in reducing postnatal depression and anxiety in Nigerian mothers. A fully powered RCT is recommended to evaluate the clinical and cost-effectiveness of LTP+CaCBT, including the child’s outcomes compared with ETAU.Clinical trial registrationhttps://clinicaltrials.gov/study/NCT04644081, identifier NCT04644081.